2018
DOI: 10.1016/j.chemgeo.2018.01.025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bacterial growth phase and culture concentration on U(VI) removal from aqueous solution

Abstract: Bacteria play a key role in controlling the mobility of contaminants, such as uranium (U), in the environment. Uranium could be sourced from disposed radioactive waste, derived either from surface disposal trenches for Low Level Waste (LLW) that, because of the waste type and disposal concept, would typically present acidic conditions (both aerobic and anaerobic), or from the geological disposal of LLW or Intermediate Level Waste (ILW) that, because of the waste type and the disposal concept, would typically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We first conducted control experiments with no DFOB added to reproduce the U VI precipitation observed in previous research at pH 11.5 and ionic strength of 0.1 M [13,14,33]. At equilibrium, we observed that only 4 to 5% of U VI was present in the solution after it was filtered through 0.2, 0.45 and 1 μm nylon filter membranes (Fig.…”
Section: Three-day Batch Experimentsmentioning
confidence: 92%
See 2 more Smart Citations
“…We first conducted control experiments with no DFOB added to reproduce the U VI precipitation observed in previous research at pH 11.5 and ionic strength of 0.1 M [13,14,33]. At equilibrium, we observed that only 4 to 5% of U VI was present in the solution after it was filtered through 0.2, 0.45 and 1 μm nylon filter membranes (Fig.…”
Section: Three-day Batch Experimentsmentioning
confidence: 92%
“…The aim of this pilot study was to study whether DFOB, a siderophore typically found in the environment, prevents the U VI precipitation in alkaline NaCl solutions observed during previous studies [13,14,33] and to determine the possible controls of concentration and reaction time. Three types of experiments were conducted: a control experiment, a precipitation inhibition experiment, and a dissolution experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Siderophores, in particular, are not limited to iron as they have been shown to form complexes with various other environmentally significant metals, including copper, nickel, zinc, americium, plutonium, and uranium [21,22]. Metal mobility has been altered by siderophores in the environment disproportionately to their concentration, making them an overlooked key component to the fate of contaminants in the environment [23]. Desferrioxamine B (DFOB) is naturally biosynthesized by fungi and bacteria in many ecosystems as a linear siderophore with three bidentate hydroxamic acid functional groups and a terminal amine that plays a key role during environmental sorption (Figure 1) [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%